2016
DOI: 10.1080/00220388.2015.1126255
|View full text |Cite
|
Sign up to set email alerts
|

Do Transnational Links Matter after Return? Labour Market Participation among Ghanaian Return Migrants

Abstract: Previous studies on transnationalism have looked at 'remittances' and 'short-term visits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…These participants were purposively selected from the city of Accra-a primary destination for different migrants both local and international (cf. Setrana & Tonah, 2016). While four of the participants had made two failed attempts, all the other three had made one attempt to migrate to Europe or North America.…”
Section: Study Context Research Methods and Profile Of The Participantsmentioning
confidence: 99%
“…These participants were purposively selected from the city of Accra-a primary destination for different migrants both local and international (cf. Setrana & Tonah, 2016). While four of the participants had made two failed attempts, all the other three had made one attempt to migrate to Europe or North America.…”
Section: Study Context Research Methods and Profile Of The Participantsmentioning
confidence: 99%
“…This is also confirmed in the literature. In their study on pre-and post-return experiences of Ghanaian international migrants, Setrana & Tonah ( 2016 ) looked at returnees’ assets and labour market participation, and found out that many keep ties with host countries for the sake of businesses and other benefits which may not be available in the home country. This is also confirmed in observations by recent studies (Bob-Milliar & Bob-Milliar, 2013b ; Olivier-Mensah, 2019 ; Olivier-Mensah & Scholl-Schneider, 2016 ) that, like our own research, found returnees prefer to keep options for re-emigration open.…”
Section: The Geopolitics Of Return and Reintegrationmentioning
confidence: 99%
“…There is a lack of empirical studies focusing on cultural reintegration. Setrana and Tonah (2014) studying returnees in Ghana, found that returnees faced cultural difficulties once they came back to their homeland. Return migrants often have to regain an understanding of how local structures work at home, and often face a period of adaptation due to prolonged time spent abroad, during which a realistic picture of the home context may be lost.…”
Section: Empirical Studies On Reintegration Of Return Migrantsmentioning
confidence: 99%